2016
DOI: 10.1111/jce.12909
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Measurements of CT Angiography, TEE, and Fluoroscopy of the Left Atrial Appendage for Percutaneous Closure

Abstract: All 3 imaging modalities correlated with ACP landing zone and WATCHMAN ostium measurements, with CCTA providing the largest measurements, followed by TEE and fluoroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 10 publications
8
66
1
Order By: Relevance
“…Because the LAA ostium is most commonly oval in shape, larger LAA ostial widths can often be found on 120–135 degree planes rather than at 45–90 degrees . Several studies have found that three‐dimensional (3‐D) TEE and cardiac computer tomography angiography (CCTA) more accurately assesses the true LAA ostial width, whereas 2‐D TEE may tend to underestimate the LAA orifice area …”
Section: Discussionmentioning
confidence: 99%
“…Because the LAA ostium is most commonly oval in shape, larger LAA ostial widths can often be found on 120–135 degree planes rather than at 45–90 degrees . Several studies have found that three‐dimensional (3‐D) TEE and cardiac computer tomography angiography (CCTA) more accurately assesses the true LAA ostial width, whereas 2‐D TEE may tend to underestimate the LAA orifice area …”
Section: Discussionmentioning
confidence: 99%
“…CCTA maximal LAA diameter measurements were on average 1–2 mm larger than TEE, and 2–4 mm larger than fluoroscopy. TEE diameter measurements were on average 1–2 mm larger than fluoroscopy . These studies thus show that CCTA provided the largest LAA measurements and can more accurately predict device size.…”
Section: Introductionmentioning
confidence: 65%
“…Saw et al. furthermore compared the measurements of the LAA using CT angiography, TEE, and fluoroscopy . Mohrs et al.…”
Section: Discussionmentioning
confidence: 99%